EVALUATION OF ENGINEERING STRUCTURES DEFORMATION (ACCURACY) - Malik, T.; Bryk, Ya.; Zatserkovnyi, V.; Belenok, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The construction of the model of accuracy of the measuring processes of the automated monitoring system of engineering structures deformations from the point of the theory of accuracy is considered in the article. From the point of view of the generalization of the accuracy of measurements by the automated system of engineering structures monitoring, the construction of the model of the measuring process is considered, resulting in separate characteristics and properties of the object to be investigated. In this case these are values of deformations of engineering constructions’ structures. The brief acquaintance with the automated system of monitoring of engineering structures deformations, which represents a chain of optoelectronic devices-deformation marks, which are installed on constructions of structures and fix the created line is given. The use of this system allows to solve the problem of the preventive assessment of the dynamics of local technogenic deformation in the engineering structure and thus to increase the level of technogenic safety of the personnel of the engineering structure. Compared with modern well-known methods and means for determining the engineering structures deformation, an automated deformation monitoring system has the following advantages: 1. Cross-section geodetic control of deformations (position) of elements of the full volume of engineering structure with increased accuracy. 2. Automated control of engineering structures deformations in real time, including in limited or inaccessible for visual measurements places. 3. Control of the technogenic safety of the engineering structure, prediction of the moment of the emergency, warning about the upcoming critical state (moment) of the engineering structure in real time with the accurate definition of a certain area. 4. Installation of the entire monitoring system occurs during the construction of the structure, pre-installation sites of optoelectronic devices - deformation marks are agreed with the designers and architects. 5. The mean square error of measurement of relative deviations of deformations is not less than 0,1 ÷ 0,5 mm at distances between optoelectronic devices up to 10 m. 6. Information on the magnitude of deviations from the nominal (initial) position goes to the remote central control panel of the system in real time scale. 7. In the case of upcoming moment of dangerous deviation (deformation), the command from the main control panel receives a signal for rapid response with the accurate designation of the place of dangerous deformation.